The global change impacts on forest natural resources in Central Rif Mountains in northern Morocco: extensive exploration and planning perspective - El Motaki, Hanifa (2019)
The global changes including social, environment and economic transformation constitute a major handicap to the sustainable development of the Moroccan Central Rif mountains area. The accelerated degradation of the forest resources in this area demonstrates that there is a dynamic interaction between the biosphere and community groups. These ever-changing interactions between the need to live and the limited of natural environment skills, give rise to environments that have been developed, built or, in general, altered or degraded. The available statistical data, cartography, field surveys and visits have shown a regression of forest superficies in the profits of the new types of illegal farming, despite the national and international development programs had established since the 1960s.